Motivation and Perfectionism in Successful and Unsuccessful Karate Athletes in Iran men's Karate Super League - Sadegh Ranjbar; Hassan Gharayagh Zandi; Sayyed Mohsen Fatemi; Ali Fadakar (University of Tehran, 2017)
Nowadays, numerous studies have shown that optimal athletic performance is related to many psychological factors. This paper aimed at comparing motivation and perfectionism of successful and unsuccessful karate athletes in Iran men's karate super league. This study was casual-comparative and the population consisted of karate athletes of Iran men's karate super league in 2015 in Kumite section. Primary data were collected by convenience sampling method from 70 athletes of all participating teams (especially two high ranking teams and three low-ranking teams) in karate super league. After collecting the data of the number of competitions and their results for each athlete, the optimal performance of karate athletes was calculated and two successful and unsuccessful groups were determined (each group 30 subjects). The demographic questionnaire, the sport motivation scale, and the sport perfectionism scale were used in this study. The K-S and Shapiro-Wilk tests were used to investigate the natural distribution of data. The results of independent t test showed a statistically significant difference in adaptive perfectionism (positive) between successful and unsuccessful athletes. However, there was no significant difference in maladaptive perfectionism (negative) between the two groups. Furthermore, the Mann-Whitney U test results showed that the difference in all motivation subscales was not significant between successful and unsuccessful karate athletes. Finally, it can be stated that some findings emphasize the role of psychological characteristics in sport success and performance in the two groups which have in the highest rank of Asian and world karate.